In-plane low thermal expansion of NiTi via controlled cross rolling. (1st February 2021) - Li, Qiao; Deng, Zhongzheng; Onuki, Yusuke; Wang, Wei; Li, Laifeng; Sun, Qingping
Abstract: Shape memory alloy (SMA) sheets processed via unidirectional rolling (UniR) exhibit macroscopic low thermal expansion (TE) over a wide temperature span but only along a certain direction. Here, we use controlled cross rolling (CroR) to achieve in-plane low coefficients of TE (CTEs) of polycrystalline NiTi sheets. It is shown that the in-plane CTEs of a CroRed NiTi sheet with the three-step rolling path (RD-15%, TD-10% and RD-5%) can be reduced close to zero within a very narrow range (-2.7 × 10 −6  K −1 to +3.0 × 10 −6  K −1 ) over a large temperature span of 223 K. The obtained in-plane CTEs are an order of magnitude smaller than those of UniRed NiTi sheets and are comparable to that of commercial FeNi Invar alloy (+2.0 × 10 −6  K −1 ). The physical origin of such in-plane low TE is explored through in situ neutron diffraction from 2.3 K to 300 K and a rule-of-mixture theoretical model. It is found that in the CroRed nanostructured NiTi, the in-plane positive TEs of textured B2 and B19' aggregates are compensated by the in-plane negative TE caused by the continuous formation (vanishing) of { 102 } 〈 U V W 〉 fiber-textured B19' variants in cooling (heating), thereby leading to the overall in-plane low TE. Such compensation mechanism in CroR can also be used to achieve in-plane low TE of other SMAs. Graphical abstracts: Image, graphical abstract